2021
DOI: 10.1097/mao.0000000000003216
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Comorbidity Between Cases of Acute Peripheral Vestibulopathies and COVID-19

Abstract: Importance:An infective etiology of acute peripheral vestibulopathy (APV) has long been hypothesized. In the context of coronavirus disease 2019 (COVID-19), we examined the possible comorbidity between these two entities.Objectives:APV is the second most common cause of vestibular disorders and results from a sudden and unilateral loss of vestibular inputs. The characteristic signs and symptoms include sudden and prolonged vertigo, absence of auditory symptoms, and absence of other neurological symptoms. An in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
1
4
0
1
Order By: Relevance
“…There are several case reports of VN following COVID-19 infection; however, the details of vestibular function examinations including caloric testing, video head impulse testing, or VEMP testing were not described in these reports [34][35][36][37] except for one report [11], and further studies evaluating the risk of VN after COVID-19 infection or VN after COVID-19 vaccination including the results of vestibular function examinations are required. A retrospective study analyzing acute peripheral vestibulopathies (APV) reported no correlation between APV and COVID-19 [38]. No statistically significant increase in VN cases in the 2020 COVID-19 pandemic season compared to 2019 was observed, consistent with this previous study.…”
Section: Discussionsupporting
confidence: 87%
“…There are several case reports of VN following COVID-19 infection; however, the details of vestibular function examinations including caloric testing, video head impulse testing, or VEMP testing were not described in these reports [34][35][36][37] except for one report [11], and further studies evaluating the risk of VN after COVID-19 infection or VN after COVID-19 vaccination including the results of vestibular function examinations are required. A retrospective study analyzing acute peripheral vestibulopathies (APV) reported no correlation between APV and COVID-19 [38]. No statistically significant increase in VN cases in the 2020 COVID-19 pandemic season compared to 2019 was observed, consistent with this previous study.…”
Section: Discussionsupporting
confidence: 87%
“…This dissemination can also lead to direct infection, inflammation responses or related vascular damage owing to vasculitis, hypercoagulability with microvascular ischemia and endothelial dysfunction in the audio-vestibular system [22,44,55,60,[70][71][72]. Autoimmune mechanism with cross-reactions of antibodies or T-cells, misidentifying inner ear antigens as the virus, has been also suggested [26,62,63,67,73]. The herpes simplex virus reactivation is thought to be another cause [22,26,57,62,63].…”
Section: Discussionmentioning
confidence: 99%
“…6 Nevertheless, not all studies support an increased incidence of co-existing vertigo and coronavirus infection. 11 Among cases of vertigo, many fulfil the criteria of vestibular neuronitis. As with other neurotropic viruses responsible for vestibular neuronitis, Covid-19 may directly damage the nerves, intruding into them via the angiotensin receptor, 12 or it may damage them indirectly through the immune system's reaction.…”
Section: Discussionmentioning
confidence: 99%
“…6 Nevertheless, not all studies support an increased incidence of co-existing vertigo and coronavirus infection. 11 Among cases of vertigo, many fulfil the criteria of vestibular neuronitis.
Dizziness is common in coronavirus disease 2019 (Covid-19), affecting about 8 per cent of patients The disease may directly damage nerves, intruding into them via the angiotensin receptor or damage them indirectly through the immune system's reaction Evidence indicates that both Covid-19 infection and the vaccination may induce vestibular hypofunction, known as vestibular neuronitis Most Covid-19 patients with vestibular neuronitis have been treated with supportive measures and corticosteroids Vestibular neuronitis with Covid-19 infection may occur even in paediatrics, as in our case Increased vestibular neuronitis during the Covid-19 pandemic is expected; conversely, Covid-19 should be considered in patients with sudden vestibular symptoms
…”
Section: Discussionmentioning
confidence: 99%